Cause of Preterm Birth as a Prognostic Factor for Mortality. Issue 1 (January 2016) - Delorme, Pierre; Goffinet, François; Ancel, Pierre-Yves; Foix-L'Hélias, Laurence; Langer, Bruno; Lebeaux, Cécile; Marchand, Laetitia Martin; Zeitlin, Jennifer; Ego, Anne; Arnaud, Catherine; Vayssiere, Christophe; Lorthe, Elsa; et al.
Abstract : OBJECTIVE: To investigate the association of the cause of preterm birth on in-hospital mortality of preterm neonates born from 24 to 34 weeks of gestation. METHODS: L'Etude épidémiologique sur les petits âges gestationnels (EPIPAGE)-2 is a prospective, nationwide, population-based cohort of very preterm births. After dividing causes of preterm birth into six mutually exclusive groups, we analyzed the association of each cause with in-hospital deaths of preterm neonates born alive with adjustment for organizational, maternal, and obstetric factors. RESULTS: The analysis included 3, 138 singleton live births from 24 to 34 weeks of gestation with a newborn in-hospital mortality rate of 5.0% (95% confidence interval 4.5–5.7). Preterm labor was the most frequent cause of preterm birth (n=1, 293 [43.5%]) followed by preterm premature rupture of membranes (n=765 [23.9%]), hypertensive disorders without suspected fetal growth restriction (n=397 [12.7%]), hypertensive disorders with suspected fetal growth restriction (n=408 [10.9%]), placental abruption after an uncomplicated pregnancy (n=92 [3.0%]), and suspected fetal growth restriction without hypertensive disorders (n=183 [5.9%]). Neonates born because of suspected fetal growth restriction with or without hypertensive disorders (adjusted odds ratio [OR] 3.0 [1.9–4.7] and adjusted OR 2.3 [1.1–4.6], respectively) had higher adjusted risks of in-hospital death than those born after preterm labor. Risks of in-hospital mortality for preterm births caused by preterm premature rupture of membranes (adjusted OR 1.3 [0.9–1.9]), hypertensive disorders without fetal growth restriction (adjusted OR 0.7 [0.4–1.4]), or placental abruption (adjusted OR 1.6 [0.7–3.7]) were similar to those born after preterm labor. CONCLUSION: Among neonates born alive before 34 weeks of gestation, only those born because of suspected fetal growth restriction have a higher mortality risk than those born after preterm labor. Abstract : Among neonates born alive before 34 weeks of gestation, only those born because of suspected fetal growth restriction have a higher mortality risk than those born after preterm labor.